Crucial functions of gut microbiota on gut–liver repair - Yamei Wang; Huining Yan; Qianqian Zheng; Xun Sun (hLife)
The gut microbiota exert a critical influence on the gut–liver axis by facilitating intestinal and hepatic repair via intricate bidirectional mechanisms. Inflammatory bowel disease (IBD), metabolic-associated steatohepatitis (MASH), and the gut–liver axis exemplify the complex interplay between the gut microbiota and hepatic function. This review explores the interplay between microbial metabolites and their roles in maintaining intestinal integrity and promoting liver regeneration. Emerging evidence shows that gut microbiota support intestinal and liver health by modulating immune responses via microbial metabolites and interactions with host immune cells. Moreover, advances in personalized therapies, including probiotics, prebiotics, and fecal microbiota transplantation (FMT), could potentially restore microbial balance and enhance tissue repair. Understanding these relationships presents opportunities for innovative interventions to improve gut and liver health, particularly in individuals with metabolic disorders.